The Human Resource Development Strategies in Improving Employee Performance in Cooperatives - Nawir Yuslem; Sugianto Sugianto; Reza Nurul Ichsan (Program Magister (S2) Kenotariatan, Fakultas Hukum, Universitas Islam Sultan Agung, 2022)
This research aims to find out and analyze human resource management strategies in improving employee performance in cooperatives and determine the results of SWOT analysis of employee performance improvement strategies with IFAS and EFAS matrix can be identified important factors both from the external environment and the internal environment that become strengths, weaknesses, opportunities and threats from improved performance. The research conducted in this study was qualitative descriptive using SWOT analysis. From the results of the analysis obtained growth strategy or growth oriented strategy, this strategy signifies the state of the company that is strong and able to continue to grow by taking opportunities and opportunities that exist. To achieve maximum turnover. This strategy was chosen because the calculation results are in quadrant I where the total weighted score of weaknesses is 2.710504 while the total weighted score of the opportunity-threat 2.653142. The position on this quadrant is very profitable and can be applied to the maximum.